Tillage-based nutrient management practices for sustaining productivity and soil health in the soybean-wheat cropping system in Vertisols of the Indian semi-arid tropics - Meena, Satya Narayan; Sharma, Shanti Kumar; Singh, Pratap; Ram, Asha; Meena, Bharat Prakash; Jain, Devendra; Singh, Deepak; Debnath, Sovan; Yadav, Suman; Dhakad, Uditi; Verma, Preeti; Meena, Jitendra Kumar; et al. (Frontiers in Sustainable Food Systems, 2023)
To achieve higher crop production in a soybean-wheat cropping system, comprehensive knowledge of soil fertility status and its variability is crucial. However, a significant gap exists between the potential and actual productivity of this system in the Vertisols of Indian semi-arid tropics. Therefore, 2 years of field research were conducted to investigate how different crop management practices affect soil fertility in this cropping system. The trial was conducted using a randomized complete block design (RCBD) with five crop management practices: CAO (conservation tillage + organic nutrient and weed management), CAC (conservation tillage + chemical nutrient and weed management), CTC (conventional tillage + chemical nutrient and weed management), OCT (conventional tillage + organic nutrient and weed management), and PoPs (package of practices). Results showed that CAO significantly (p < 0.05) increased soil organic C (6.8 g kg−1), available N (129.5 mg kg−1), P (11.0 mg kg−1), K (232.6 mg kg−1), Fe (9.17 mg kg−1), and Mn (10.48 mg kg−1) at topsoil (0–15 cm) and deeper layers (15–60 cm). In contrast, CAC had significantly (p < 0.05) higher soil availability of Ca (5,072 mg kg−1) and Mg (901 mg kg−1) and Cu (0.84 mg kg−1). On the other side, PoPs resulted in the highest S (10.05 mg kg−1) and Zn (0.85 mg kg−1) availability in the topsoil. Our results evidently suggested S and Zn availability as key indicators of soil health sustenance in the present agroecosystem. Notably, CAC had significantly (p < 0.05) higher system productivity (4.62 t ha−1) than the other treatments, showing a 14.0, 6.3, and 18.2% increase over CAO, CTC, and OCT, respectively. Based on the results, it is recommended that CAC is a better option for achieving higher system productivity, while CAO is the best option for ensuring long-term sustainability of soil fertility. The findings of this study could be useful for farmers and agricultural researchers in designing efficient crop management practices to improve the productivity and sustainability of soybean-wheat cropping system in arid to semiarid ecology.